The Liberation Hypothesis Perspective and Juvenile Court Outcomes: implications for an Understanding of the Interplay Between Offender and Offense Characteristics - Beaudry-Cyr, Maude (Crime & delinquency, 2020)
Extensive empirical support demonstrates the importance of legal (e.g., crime severity, prior record) and extralegal factors (e.g., race/ethnicity, gender) in predicting juvenile court outcomes. An understudied area is inquiry into how certain extralegal factors interact with legal determinants to impact the social control of juveniles. This study uses a sample of delinquent referrals from a Northeast state over 10 years to examine the impact of race/ethnicity, gender, crime severity, and prior record, individually and in combination, on juvenile court outcomes. Although the liberation hypothesis predicts that extralegal factors have a diminishing effect on case outcomes as the severity of the case increases, overall, we fail to find support for this expectation.